THE ROLE OF EARLY DETECTION OF AGGRESSIVE PERIODONTITIS: PERAN DETEKSI DINI PADA PERIODONTITIS AGRESIF - Sarah, Maria Meylinda (Dentika: Dental Journal, 2016)
Aggressive periodontitis belongs to a group of periodontal disease that develops rapidly and occurs in healthy individuals and is associated with heredity. The purpose of this article is to find out the causes, characteristics and treatment of aggressive periodontitis. Aggressive periodontitis is characterized by an increased number of bacteria Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis. Clinically there is a plaque that forms a thin layer on the tooth surface. Initial symptoms are found in mobility and pathologic migration of first molar and incisors. Treatment of aggressive periodontitis is by administering antibiotics accompanied by scaling and root planing. Instruction to maintain oral hygiene should be emphasized to the patient. Tooth extraction is done if the prognosis is not good. The diagnosis of aggressive periodontitis can be established by examining the history of the disease, clinical examination includes examination of pocket depth and examination of attachment loss and supported by radiographic examination. Aggressive periodontitis has hereditary tendency, therefore the patient’s siblings and families should be included in the examination of this disease.